Design of high lifetime suspension plasma sprayed thermal barrier coatings. Issue 3 (March 2020) - Gupta, M.; Li, X.-H.; Markocsan, N.; Kjellman, B.
Abstract: Thermal barrier coatings (TBCs) fabricated by suspension plasma spraying (SPS) have shown improved performance due to their low thermal conductivity and high durability along with relatively low production cost. Improvements in SPS TBCs that could further enhance their lifetime would lead to their widespread industrialisation. The objective of this study was to design a SPS TBC system with optimised topcoat microstructure and topcoat–bondcoat interface, combined with appropriate bondcoat microstructure and chemistry, which could exhibit high cyclic lifetime. Bondcoat deposition processes investigated in this study were high velocity air fuel (HVAF) spraying, high velocity oxy fuel spraying, vacuum plasma spraying, and diffusion process. Topcoat microstructure with high column density along with smooth topcoat–bondcoat interface and oxidation resistant bondcoat was shown as a favourable design for significant improvements in the lifetime of SPS TBCs. HVAF sprayed bondcoat treated by shot peening and grit blasting was shown to create this favourable design.